Treatment of neuropathic pain with repeated low-dose MDMA: a case report - Gasser, Peter; Liechti, Matthias E.; Holze, Friederike (Frontiers in Psychiatry, 2025)
A 64-year-old male patient who suffered from traumatic life experiences and neuropathic pain after oncological chemotherapy was treated with medium to high doses of lysergic acid diethylamide (LSD) and high doses and microdoses of methylenedioxymethamphetamine (MDMA). At the beginning of treatment, the patient did not experience any acute subjective effects of LSD at a dose of 200 µg. After increasing the LSD dose to 400 µg, he experienced subjective acute effects, and the first lasting therapeutic effects were observed. After changing from LSD to MDMA at both high doses (150-175 mg) and repeated low doses (12.5-25 mg), the patient exhibited marked improvements in neuropathic pain that were sustained even after stopping repeated MDMA treatment. MDMA mini/microdosing has not yet been broadly investigated. This case documents benefits of low doses of MDMA for the treatment of a pain disorder. Further research is needed on effects of MDMA on pain.